Toward an Evolutionary Theory of Shadow Options: Emergent Functions of Corning’s Glass-Based Innovations - Andriani, Pierpaolo; Cattani, Gino (Organization Science, 2024)
By integrating Herbert Simon’s theory of artifact and Brian Arthur’s concept of functionality in technology, we propose a novel conceptual framework for analyzing the process by which shadow options embedded in a firm’s existing technologies emerge and are converted into real options. We apply this framework to examine the shadow options of Corning’s photosensitive glass technologies. The core of our model is that technologies subsume options, most of which are shadow because they refer to functions of those resources that were unknown when they were originally acquired or created. Shadow options are hidden in functionalities. Functionalities and functions are relational entities that exist at the interface between an artifact’s inner and outer environments. The transformation of shadow into real options occurs along a continuum, with two distinct types represented at its extremes: the Schumpeterian and Kirznerian types. We examine organizational attributes that enable Schumpeterian and Kirznerian shadow options and explain how firms can systematically pursue an innovation strategy that exploits the shadow options embedded in their technologies.